جماليات التناص في ديــوان " همسات للريح وأخرى للمطر " ليوسف وغليسي - مناعي، ابراهيم الخليل (جامعة الوادي University of Eloued, 2019)
تناول البحث جماليات التناص في ديوان الشاعر الجزائري يوسف وغليسي ، حيث تفاعل مع عديد القصص الدينية و الآيات القرآنية و هذا دليل على تشبعه بالثقافة الإسلامية ، حيث أنه استقى العديد من أفكاره و معانيه من النصوص الدينية و خاصة من القرآن الكريم ، كما لم يخلو الديوان من الإيحاءات التاريخية و الأسطورية مما يوحي لنا بالثقافة الواسعة التي يتمتع بها الشاعر و التي ضمنها في ديوانه . وقد اشتمل البحث على مقدمة و مدخل و فصلين ، حيث تناولنا في المدخل الحديث عن التناص عند الغرب و العرب مع ذكر روادهما و أهم أعلامهما ، أما الفصل الأول فكان موسوما بــ : " التناص ماهيته أدواته و صورته " وقد قسمناه إلى مبحثين تناولنا في المبحث الأول منهما : مفهومه ، آلياته ومستوياته ، وفي المبحث الثاني عالجنا : أشكاله ، مظاهره ، ومصادره . في حين كان الفصل الثاني تطبيقي وقد حمل عنوان : " تجليات التناص في ديوان همسات الريح " وقد قسمناه إلى مبحثين تناولنا في المبحث الأول منهما التعريف بالشاعر و الديوان وفي البحث الثاني : عالجنا تجليات التناص في شعره من خلال مصادر التناص ، فتطرقنا إلى التناص الديني خاصة مع القرآن الكريم ، ثم عرجنا على التناص التاريخي ثم التناص الأسطوري . وفي الأخير ذيلنا بحثنا بخاتمة ضمناها أهم النتائج التي توصلنا إليها . The study dealt with the aesthetics of harmony in the library of the Algerian poet Youssef wagleissi, where he interacted with many religious stories and Quranic verses. This is evidence of his saturation in the Islamic culture, as he derived many of his ideas and meanings from the religious texts, especially from the Holy Quran. Historical and mythological implications, suggesting to us the wide culture enjoyed by the poet, which he included in his office. The first chapter was characterized by: "the relationship between its tools and its image" and we divided it into two subjects we dealt with in the first subject Including: its concept, mechanisms and levels, and in the second dealt with: its forms, manifestations, and sources . While the second chapter was applied, and it was titled: "The manifestations of harmony in the office of the whispers of the wind" and we divided it into two sections, we dealt with the first part of them, the definition of the poet and the Diwan and in the second research: We dealt with manifestations of harmony in his poetry through sources of harmony, With the Holy Quran, and then we overcome the historical harmony and then legendary harmony In conclusion, we looked at the conclusion that we included in our most important conclusions
Keywords: جماليات التناص ،ديوان همسات للريح و أخرى للمطر ، التفاعل النصي; The aesthetics of harmony, the whispers of the wind and another of the rain, text interaction